Clinical Simulation in Complexity: Simulation-Based Learning for Medical Training - Laverde, Andrés Chiappe; Álvarez Ricardo Andrés Novoa; Álvarez Thiago Andrés Navarro; Parra, Sandra Liliana Navarro (Journal of Posthumanism, 2025)
The social isolation and distancing measures which followed the COVID-19 pandemic promoted clinical telesimulation and virtual simulation as a didactic strategy for training medical students. These strategies have not yet been fully evaluated in terms of impact and acceptability. This study evaluates virtual simulation and telesimulation strategies applied during the pandemic from the perspective of students, professors, and experts in clinical simulation. A qualitative method was applied to 56 medical students studying semiology and 12 professors. The students and professors conducted clinical simulations during in-person classes assisted by information and communication technology (ICT). Follow-up was conducted for 18 months. The intervention focused on tele-simulation and in-person ICT-assisted classes. The measurements focused on students’ perceptions of the practice and of professors relating to developing skills and competence. During remote debriefing, students gave simulations an average rating of 6.43/7. Measuring the competence development (generic and specific) showed a rate of 82.2% at different times during the simulation, corresponding to the 80% level of development given by professors’ evaluations in real scenarios. Using a simulation-based didactic strategy in the form of ICT-assisted in-person classes prior to the practical training stage required for medical students was pertinent, efficient, and found to be favourable during the pandemic. Including this innovative strategy in the curriculum, even after returning to in-person classes, is recommended because it offers academic support in training doctors and developing high-level competencies.